Current Studies into the Genotoxic Effects of Nanomaterials - Cheng-Teng Ng; Jasmine J. Li; Boon-Huat Bay; Lin-Yue Lanry Yung (Journal of Nucleic Acids)
Nanotechnology has created opportunities for engineers to manufacture superior and more efficient devices and products. Nanomaterials (NMs) are now widely used in consumer products as well as for research applications. However, while the lists of known toxic effects of nanomaterials and nanoparticles (NPs) continue to grow, there is still a vast gap in our knowledge about the genotoxicity of NMs. In this paper, we highlight some NMs of interest and discuss the current in vivo and in vitro studies into genotoxic effects of NMs.